Cultivated and wild juvenile thick‐lipped grey mullet, Chelon labrosus: A comparison from a nutritional point of view - García-Márquez, Jorge; Galafat, Alba; Alarcón, Francisco Javier; López-Figueroa, Félix; Martínez-Manzanares, Eduardo; Arijo-Andrade, Salvador; Abdala-Díaz, Roberto Teófilo (MDPI, 2021)
The thick-lipped grey mullet (Chelon labrosus) is a nominee fish species for aquaculture diversification in Spain because it is an omnivore and euryhaline species, but limited knowledge about the nutritional attributes of this species is available. This study aimed to characterize the chemical composition of wild and cultured fish. The muscle proximate composition, and fatty acid and amino acid profiles were assessed. The cultivated specimens showed a higher lipid content and lower protein and ash contents compared with the wild specimens. The predominant tissue fatty acids in both the wild and cultivated fish were palmitic acid (16:0), oleic acid (18:1n-9) and docosahexaenoic acid (DHA, 22:6n-3). A higher content of arachidonic acid (ARA, 20:4n-6), eicosapentaenoic acid (20:5n-3) and DHA were detected in the muscle of wild mullets, while the fish supplied with commercial pellets showed higher quantities of monounsaturated fatty acids, and lower quantities of saturated fatty acids and polyunsaturated fatty acids (PUFAs). Regarding PUFAs, n-3 fatty acids were predominant in wild mullets, while n-6 and n-9 were more abundant in farmed fish. In terms of amino acid composition, except for histidine in wild specimens, the amino acid amounts were higher than the FAO/WHO standard. In conclusion, C. labrosus may contribute to improving the dietary intake of highly polyunsaturated n-3 fatty acids, with a benefit to human health, owing to that fact that a 100-g fillet portion of cultivated and wild C. labrosus can provide 770 mg and 1160 mg of EPA and DHA, respectively, which exceeds the 250 mg dietary daily intake recommended by the FAO/WHO.
Keywords: Peces - Composición; Peces - Alimentación; Acuicultura; Amino acids; Chelon labrosus; Fatty acids; Proximate analysis